Neurocognitive impairment and its associated factors among patients with diabetes mellitus who have follow up at referral hospital in Northwest, Ethiopia - Simachew, Arefaynie; Getnet, Asmamaw; Minwuyelet, Fentahun; Mitiku, Haymanot Zeleke; Kebede, Worku Misganaw; Bizuneh, Fassikaw Kebede; Tiruneh, Bekele Getenet; Tsegaye, Dejen (Frontiers in Endocrinology, 2024)
Background: Neurocognitive impairment is a condition that makes it difficult for a person to make decisions that affect memory, learning new things, concentration on daily activities, and can range from mild to severe forms. It is a major health problem, less known and less addressed complication of diabetes mellitus.The aim of the study is to assess prevalence of neurocognitive impairment and associated factors among diabetic mellitus patients.We conducted an institutional-based cross-sectional study involving 512 diabetic patients under follow-up at XXX Specialized Hospital from March 1 to April 30, 2023.Data on cognition, behavior, and depression were collected using standardized tools, including the Mini Mental State Examination for cognition, the CAGE assessment tool for alcohol-related behavior, and the PHQ-9 for depression. These assessments were conducted through face-to-face interviews and chart reviews. A diagnosis of diabetes is confirmed in adults when fasting blood glucose levels exceed 126 mg/dl in three consecutive follow-up measurements. Data entry was performed using Epidata version 4.6, and analysis was conducted using SPSS version 26.Variables with a P-value < 0.25 in bivariate analysis were included in multivariable logistic regression. Statistical significance was set at P ≤ 0.05 with a 95% CI. Results were presented using tables, graphs, and descriptive text.: The prevalence of neurocognitive impairment among diabetic patients at XXX Comprehensive Specialized Hospital was 28.3% [95% CI: 24.57-32.39]. Factors associated with this impairment included being female (AOR=2.29 [95% CI: 1.43-3.67]), rural residence (AOR=3.16 [95% CI: 2.01-4.95]), comorbidity (AOR=3.30 [95% CI: 2.08-5.23]), diabetes duration of 6-10 years (AOR=1.72 [95% CI: 1.01-2.94]), diabetes duration >10 years, and blood sugar level >126 mg/dl (AOR=2.25 [95% CI: 1.42-3.57]).Patients are encouraged to adhere to proper medication regimens to effectively control their blood glucose levels.This study found a high prevalence of neurocognitive impairment (NCI) among diabetic patients, affecting about one-fourth based on MMSE scores. Key risk factors identified include female gender, rural residence, comorbidities, longer duration of diabetes, and elevated blood glucose levels.